An Analysis of the Effects of Corona Virus (COVID-19) on International Financial Derivatives Market, 2020 - Afrina, Taskin; Beg, Tahrima Haque; Zayed, Nurul Mohammad; Hossain, Md Shakib; Shahi, Shahiduzzaman Khan (Indian Journal of Finance and Banking, 2020)
This research article develops a rational framework to comprehend the spatiotemporal structures of epidemic illness (COVID-19) incident, its applicability, and its significances to financial markets action. The article proposes a paradigm shift which is a new multidimensional geometric approach that has to apprehend all proportional and asymmetrical strategic illustrated tendencies. The epidemic impact on economic activity differs in terms of magnitude and intensity: an economy experiences a supply and demand shocks in the short-run with instant effects in output and employment. This has generated unparalleled amounts of vulnerability, which is a relatively limited amount of time that has incurred substantial risks to investors. This paper seeks to chart the general dynamics of global derivatives markets with country-specific threats and structural threats. The COVID-19 catastrophe has accelerated crucial disturbances for exchange rates and international capital cycles. Cross-border portfolio investment halted in many developing markets as well as in some progressive economies in 2020. All show that in this pandemic situation coronavirus affects financial markets and extreme volatility in the financial market. Nations have not had to utilize capital supervision. To assistance foreign currency liquidity, numerous developing markets have negotiated in the foreign exchange market and slowed down regulations on capital influxes. The globalization of financial markets is directed to the gigantic expansion of magnitude and diversification of financial trades. Finally, all sections show and describe in detail this topic and give some recommendations to overcome this situation.